Synthesis and characterization of peptide-imprinted nanogels of controllable size and affinity. (December 2018) - Cenci, Lucia; Tatti, Roberta; Tognato, Riccardo; Ambrosi, Emmanuele; Piotto, Chiara; Bossi, Alessandra Maria
Graphical abstract: Highlights: Modulate "at-will" the size of the nanogels playing on monomer composition. I mprint a single binding site per nanogel playing on total monomer to template molar ratio. Produce nanomolar affinity nanogel for the recognition of Troponin I peptide. Abstract: Molecularly imprinted polymeric nanogels (nanoMIPs) are soft biomimetics with recognition properties similar to antibodies but robustness and integrability to devices (sensing, assays) typical of polymers. Aiming at tailor-made at-will the recognition and physical properties of these biomimetics, we investigated the process of stamping analytes of clinical relevance, i.e. an idiotipic peptide of Troponin I, on protein-compatible soft-material at the nanoscale. Highly crosslinked poly(acrylamide- co -methacrylic acid) nanoparticles were prepared by precipitation polymerization via free radical initiation. The influence of the monomer composition to the nanogel hydrodynamic size was observed by dynamic light scattering and scanning electron microscopy. The effect of the total monomers to template (TM:T) molar ratio on the formation of the binding sites was investigated thermodynamically. Results indicate rules for the manipulation of the nanogel sizes, showing the pivotal role of hydrophobic interactions in confining the polymerization to the nanoscale (∼60 nm). The efficacy of the stamping process in the chosen polymerization conditions resulted maximal for TM:T molar ratios in the range 175:1–437:1. NanoMIPs with nanomolar dissociation constants for the template and a mean number of one binding site per particle were produced. Overall the results set conditions for preparing synthetic recognition nanoparticles acting as peptide-recognition elements.